Immune Defenses of a Beneficial Pest: The Mealworm Beetle, Tenebrio molitor - Vigneron, Aurélien; Jehan, Charly; Rigaud, Thierry; Moret, Yannick (Frontiers in Physiology, 2019)
The mealworm beetle, Tenebrio molitor, is currently considered as a pest when infesting stored grains or grain products. However, mealworms might be now promoted as to beneficial insect, because they contain significant nutrient that makes them viable as food and feed, and they were discovered capable of degrading polystyrene and plastic waste. This insect is therefore raising considerable interest for being produced at an industrial scale, which may promote disease transmission within the insect cultures. Disease resistance is of paramount importance for both the control and the culture of mealworms, and several biotic and abiotic environmental factors were found to affect the success of their anti-parasitic defenses, either positively or negatively. After providing a detailed description of the anti-parasitic defenses of T. molitor, we review the main biotic and abiotic environmental factors altering their expression and discussed their implications for the purpose of controlling the development and health of this insect.